Investigation into use of Drugs in Wrong Nervous System Indications Among Students in Chittagong city of Bangladesh: A Comparison Between Medical and Nonmedical Students - Chowdhury, Nishat (International Journal of Psychosocial Rehabilitation, 2013)
All kinds of drugs are available over the counter in Bangladesh. The objective of this study was to investigate the over the counter use of self-medicated drugs targeting nervous system among medical and nonmedical students. By snowball sampling method, 101 medical students and 186 nonmedical students were found who used at least one of the ９ drugs (be- lieved as antipsychotics among nonmedical people) under survey within 6 months prior to survey date. The nine drugs used for survey were Domeperidone, Sertraline, Amitriptyline, Midazolam, Diazepam, Bromazepam, Flupentixol-melitracen and Clonazepam. The symptoms, diseases etc. of the students and the length of therapies they had followed for the respect- ive drugs were noted. Among nonmedical students, several cases were found where drugs were being self medicated in wrong indications, for example, use of flupentixol-melitracen and domeperidone to treat headache. The nonmedical stu- dents chose the fast acting drugs having the strongest effects for self medication.